Beneficial effect of Gyejibokryeong-hwan on climacteric syndrome with blood stasis pattern: A randomized, double-blinded, placebo-controlled clinical pilot trial - Kyungsun Han; Jeong-Eun Yoo; Jung-Eun Kim; Ojin Kwon; Ae-Ran Kim; Hyo-Ju Park; So-Young Jung; Mikyung Kim; Changsop Yang; Jung-Hyo Cho; Jun-Hwan Lee (Integrative Medicine Research)
Background: Gyejibokryeong-hwan (GBH), a herbal mixture that is widely used for climacteric syndrome, is studied for its efficacy; however, no study evaluated the GBH indication, which is a blood-stasis pattern based on traditional Chinese medicine theory. Methods: This was a randomized, double-blinded, placebo-controlled clinical pilot trial. Fifty subjects with climacteric syndrome were recruited and randomly assigned to GBH group or placebo group. Subjects were administered GBH or placebo granules for 4 weeks followed by 4 weeks of observation period. For the primary outcome, the Menopause Rating Scale (MRS) was evaluated. For the secondary outcomes, quality of life, degrees of abdominal resistance and tenderness, blood-stasis pattern questionnaire and degree of upward movement of Qi were evaluated. Results: After 4-week intervention, the mean change of total MRS score significantly decreased in the GBH group compared to the placebo group (p = 0.037). The quality of life related to physical health (p = 0.008) and blood-stasis pattern (p = 0.018) significantly improved in the GBH group but not in the placebo group. Conclusion: Our findings provide evidence of the feasibility of recruiting subjects with GBH indications and show that GBH may have clinical efficacy for the treatment of menopausal symptoms, especially urogenital symptoms, without any significant adverse events. Trial registration: This trial was registered at Clinical Research Information Service (CRIS identifier: KCT0002040).